A Case of Persistent Pityriasis Rosea Successfully Treated by a Short Course of Therapy with Abrocitinib - Wu H; Ji QJ; Xu YY; Zhu JW (Dove Medical Press, 2024)
Hao Wu, Qing-Jie Ji, Yu-Yang Xu, Jian-Wei Zhu Department of Dermatology, Quzhou TCM Hospital at the Junction of Four Provinces Affiliated to Zhejiang Chinese Medical University, Quzhou, People's Republic of ChinaCorrespondence: Jian-Wei Zhu, Email zjwmed@163.comAbstract: Pityriasis rosea (PR) is a common inflammatory, erythematous and scaly skin condition that usually affects individuals aged from 20 to 40 years old. The disease often exhibits a self-limiting course up to 6- 8 weeks. We report a 25-year-old female patient with a six-month history of red scaly rashes on the trunk and proximal limbs, accompanied by severe pruritus that has been remained ineffective conventional treatments. She was diagnosed as persistent pityriasis rosea. As abrocitinib has been proved to be effective for many inflammatory diseases, therefore in this case, we tried abrocitinib for the patient, and a good result had been achieved.Keywords: pityriasis rosea, abrocitinib, JAK-STAT pathway